Communication apprehension among Malaysian undergraduates: A theoretical perspective - Joseph Alagiaraj T. Raj; Asmaa AlSaqqaf (ResearchGate, 2024)
One of the main reasons of poor performance of graduates in interviews is due to communication apprehension. This has resulted in unemployment in Malaysia which are caused by an excess of graduates who are unable to find jobs that align with their educational skills. Communication Apprehension or fear of public speaking need to be addressed as it can become a hindrance of pursuing careers of interest. This opinion paper deals with the theoretical aspects of communication apprehension and its connections to theories that can identify probable solutions in a South -East Asia context. Findings show that there is a link among the following theories; communication apprehension (CA), affective filter hypothesis (AFH) and self-efficacy (SE) among others act as a foundation for a theoretical framework to create a public speaking teaching module to address communication apprehension.